Vehicle routing applied to natural disasters in South América: state of art - Gutierrez Guzman, Flavio (2020)
This paper presents a literature review of the Vehicle Routing Problem (VRP) applied to natural disasters in South America. The review focuses on the last ten years (2009 - 2019), in free access and paid databases.83% are in Spanish and 17% in English. Most of the investigations deal with shipping and delivery of products, but there are also papers on programming and routing of personnel, such as volunteers, humanitarian logistics specialists, medical personnel, and military personnel. In the review, several characteristics of the problem have been taken into account, such as, the type of disaster, the VRP model used, the solution method employed, the use or not of parameters with uncertainty. The 65 % of investigations were found in databases of free access, 83 % are deterministic models, the most used model is the classic VRP, the exact solution methods are the most used, followed by the metaheuristics (mainly the genetic algorithms). It is hoped that this work will serve to give a general perspective on the application of VRP to disaster problems, as well as to serve as a background for work in this area.